Peculiarities of the Critical Thinking of Students and Possibilities of its Development - Valatkaitė-Rimienė, Vaiva (Acta Paedagogica Vilnensia, 1998)
The development of thinking takes a very important place in the educational process. It is not enough to know facts, students would be able to think critically, to estimate, to solve problems. This article presents the main principles of the theory of problem thinking developed by J. Dewey, the taxonomy of skills of knowledge classified by B. Bloom, the principles of critical thinking of G. Nosich. The research of peculiarities of thinking of students is presented in this article. This research shows that a large majority of students is not able to think critically. So teachers would give more attention to the development of critical thinking, argumentation in the problem solving process. This article gives teachers some concrete advices how to do that.
Keywords: students; critical thinking; problem solving; J. Dewey; Bloom's taxonomy